Some Aspects of the Physiology of the Nyctotherus velox, a Commensal Ciliated Protozoon Taken from the Hindgut of the Tropical Millipede Archispirostreptus gigas - Kišidayová, Svetlana; Scholcová, Nikola; Mihaliková, Katarína; Váradyová, Zora; Pristaš, Peter; Weisskopf, Stanislava; Chrudimský, Tomáš; Chroňáková, Alica; Šimek, Miloslav; Šustr, Vladimír (Life (Basel, Switzerland), 2023)
In this paper, the growth requirements, fermentation pattern, and hydrolytic enzymatic activities of anaerobic ciliates collected from the hindgut of the African tropical millipede Archispirostreptus gigas are described. Single-cell molecular analysis showed that ciliates from the millipede hindgut could be assigned to the Nyctotherus velox and a new species named N. archispirostreptae n. sp. The ciliate N. velox can grow in vitro with unspecified prokaryotic populations and various plant polysaccharides (rice starch-RS, xylan, crystalline cellulose20-CC, carboxymethylcellulose-CMC, and inulin) or without polysaccharides (NoPOS) in complex reduced medium with soluble supplements (peptone, glucose, and vitamins). Specific catalytic activity (nkat/g of protein) of α amylase of 300, xylanase of 290, carboxymethylcellulase of 190, and inulinase of 170 was present in the crude protein extract of N. velox. The highest in vitro dry matter digestibility was observed in RS and inulin after 96 h of fermentation. The highest methane concentration was observed in xylan and inulin substrates. The highest short-chain fatty acid concentration was observed in RS, inulin, and xylan. In contrast, the highest ammonia concentration was observed in NoPOS, CMC, and CC. The results indicate that starch is the preferred substrate of the N. velox. Hydrolytic enzyme activities of N. velox showed that the ciliates contribute to the fermentation of plant polysaccharides in the gut of millipedes.
Keywords: in vitro growth; enzymatic activities; tropical millipedes; ciliates; polysaccharide fermentation; hindgut protozoa; Nyctotherus